Formulative Policy on the Regulation of Abortion Crimes in the National Criminal Code: Normative Analysis and Its Implications for the Penal System in Indonesia - Cherry Laurencia Sinukaban; Rachmad Abduh (ISNU Sumatera Utara, 2026)
The regulation of the crime of abortion in the National Criminal Code (KUHP) is part of a formulative policy of criminal law that aims to balance the protection of the right to fetal life, the interests of women's reproductive health, and moral and social values living in Indonesian society. This study aims to analyze the formulative policy of regulating the crime of abortion in the National Criminal Code and its implications for the penal system in Indonesia. The research method used is normative legal research with a statutory approach, a conceptual approach, and a comparative approach. The results of the study show that the National Criminal Code reformulates the abortion offense with a more systematic and progressive regulation, especially through the recognition of certain exceptions based on medical and emergency reasons, in line with the principles of health protection and human rights. However, the policy still maintains the criminal character as the ultimate remedium through proportionate criminal threats. The implications of this regulation on the penal system can be seen in the shift in orientation from a purely repressive approach to a more humanistic and just approach, by providing space for consideration of the perpetrator's subjective condition and the purpose of correctional punishment. Therefore, this formulative policy is expected to be able to create a balance between legal certainty, justice, and usefulness in criminal law enforcement in Indonesia.